Pemanfaatan Limbah Plastik Dan Abu Sisa Pembakaran Gerabah Menjadi Paving Block Pada UMKM Dan Masyarakat Desa Banyumulek - Rosyia Wardani; Ida Ayu Nursanty; Baiq Ertin Helmida; Ulfiyani Asdiansyuri; Galuh Ratna Mutia; Putri Reno Kemala sari; M. Wahyullah; Muhammad Alamsyah; Dina Salsabilla; Oktaviana Dinistri (Valid Jurnal Pengabdian, 2024)
Assistance in utilizing plastic waste and ash from burning pottery into paving blocks is an implementation of Community Service (PKM) carried out by STIE AMM Mataram lecturers. Banyumulek Village produces waste every day in the form of plastic and the ash left from burning pottery just piles up. It is hoped that the development of creativity based on the use of ashes left over from burning pottery for all village communities can be carried out with guidance and assistance in a creative economy based on an economy made from plastic waste, the community can produce benefits and profits for the community. Making paving blocks from these two types of waste, which are often found in Banyumulek Village, is not only for making a profit, but can also provide innovation and business development among MSMEs by utilizing plastic waste and ash from burning pottery, which are often found in Banyumulek Village. In terms of marketing, MSMEs carry out promotions through social media. Currently, almost everyone uses social media, by marketing in an interesting way on social media, it will be easier to attract or captivate buyers. In this way, sales of paving block products made from plastic and also ash left over from burning pottery will be better known and it is hoped that this will have an impact on the level of sales of these products.